2001
DOI: 10.1177/039139880102401004
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxicity: Present State of the Art

Abstract: The uremic syndrome is a complex mixture of organ dysfunctions, which is attributed to the retention of a myriad of compounds that under normal condition are excreted by the healthy kidneys (uremic toxins). In the area of identification and characterization of uremic toxins and in the knowledge of their pathophysiologic importance, major steps forward have been made during recent years. The present article is a review of several of these steps, especially in the area of information about the compounds that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
201
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(206 citation statements)
references
References 300 publications
(263 reference statements)
1
201
0
4
Order By: Relevance
“…The activation of neutrophils, platelets, vascular endothelium, and factor XII (Hageman factor) leads to the production of free radical (70), cytokines (71), chemokines (72,73), proteases (74), and increased platelet adhesion (75) as well as activation of the intrinsic coagulation system, the kallikrein system, and fibrinolysis (72). Kidney injury and the subsequent reduction in glomerular filtration seem to reduce the ability of the body to remove inflammatory markers (e.g., TNF-a, IL-6, and IL-b) (76). The exact contribution of this inflammatory upregulation to kidney injury in humans undergoing cardiopulmonary bypass is not known; however, on the basis of animal data, which clearly show an inflammatory component to kidney injury (34, [77][78][79], it is assumed to be substantial (35).…”
Section: Inflammationmentioning
confidence: 99%
“…The activation of neutrophils, platelets, vascular endothelium, and factor XII (Hageman factor) leads to the production of free radical (70), cytokines (71), chemokines (72,73), proteases (74), and increased platelet adhesion (75) as well as activation of the intrinsic coagulation system, the kallikrein system, and fibrinolysis (72). Kidney injury and the subsequent reduction in glomerular filtration seem to reduce the ability of the body to remove inflammatory markers (e.g., TNF-a, IL-6, and IL-b) (76). The exact contribution of this inflammatory upregulation to kidney injury in humans undergoing cardiopulmonary bypass is not known; however, on the basis of animal data, which clearly show an inflammatory component to kidney injury (34, [77][78][79], it is assumed to be substantial (35).…”
Section: Inflammationmentioning
confidence: 99%
“…30 In this study, mean serum TC and LDL levels were similar between the low GFR and control groups. Similarly, Vanholder et al 23 and Schiavon et al 31 found no significant difference between lipid profiles of patients and control subjects.…”
Section: Discussionmentioning
confidence: 87%
“…A potential explanation for the limited correlation of biomarkers of oxidative stress and inflammation with GFR may be that many of the solutes used as biomarkers undergo renal clearance primarily via renal tubular metabolism rather than glomerular filtration. [23][24][25] However, several studies have associated changes in GFR with biomarkers of inflammation, particularly in patients with advanced disease. [26][27][28][29] National Kidney Foundation reported that oxidative stress was associated with stage 3 CKD.…”
Section: Discussionmentioning
confidence: 99%
“…2 -microglobulin, by high-flux hemodialysis is associated with a lower mortality by infectious disease (Cheung et al 2008). An increased removal of middle-sized molecules could also have positive effects of the cardiovascular system (Vanholder et al 2001;Vanholder et al 2008). In a Cochrane database review by Rabindranath et al in 2006, the authors were unable to demonstrate a significant advantage with convective therapies over low-flux hemodialysis with regard to clinical outcomes such as mortality, dialysis-related hypotension and hospitalization (Rabindranath et al 2006).…”
Section: Patients On Hemodialysismentioning
confidence: 99%